Endobronchial tuberculosis presented as multiple endobronchial vesicular lesions. Issue 2 (June 2015) - Idrees, Farah; Kamal, Saima; Irfan, Muhammad; Ahmed, Rashida
Abstract: Endobronchial tuberculosis (EBTB) is a tuberculous infection of the tracheobronchial tree with microbiological and histopathological evidence, with or without parenchymal involvement. EBTB commonly presents as acute or insidious onset cough, wheeze, low grade fever, and constitutional symptoms. In elderly patients, other differentials like malignancy and pneumonia may lead to misdiagnosis. Hence, bronchoscopy is essential for confirmation of EBTB. Here we report a rare presentation of EBTB in a 65 year old patient who presented with 3 months history of fever and cough and have multiple endobronchial vesicular lesions on bronchoscopy.